2011
DOI: 10.1007/s00467-011-1996-5
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance towards Th1 pathway predominance in purpura nephritis with proteinuria

Abstract: Although recent reports suggest a possible role for an imbalance in Th1 and Th2 proinflammatory cytokines in the development and progression of glomerulonephritis, there is little information on Th1 or Th2 predominance in Henoch-Schönlein purpura nephritis (HSPN). Since T-bet and GATA-3 are transcriptional factors that regulate the differentiation of helper T lymphocytes into Th1 and Th2, we examined the relative mRNA expression of T-bet and GATA-3 in the urinary sediment of children with proteinuric HSPN by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…15 In the present study, T-cell, B-cell and NK cell percentages and ratios in peripheral blood and serum concentrations of immunoglobulins A, M and G were measured, but no significant differences were found between HSP patients with or without nephritis. However, immune function was only tested at one timepoint; dynamic monitoring may be required to clarify the roles of the cellular and humoral immune systems in HSPN pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…15 In the present study, T-cell, B-cell and NK cell percentages and ratios in peripheral blood and serum concentrations of immunoglobulins A, M and G were measured, but no significant differences were found between HSP patients with or without nephritis. However, immune function was only tested at one timepoint; dynamic monitoring may be required to clarify the roles of the cellular and humoral immune systems in HSPN pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a non-invasive monitoring method is desirable in patients with kidney disease, especially pediatric-onset GN. Recently, it has been reported that the gene expression of functional molecules, such as transcriptional factors and proinflammatory cytokines/chemokines, in urinary sediment reflects pathogenesis and disease activity in patients with lupus nephritis (LN), IgA nephropathy (IgAN) and purpura nephritis (PN), and could be used for non-invasive monitoring of disease activity and response to treatment, without the potential demerits of invasive renal biopsy (Chan et al 2003;Wang and Szeto 2007;Tsuruga et al 2010Tsuruga et al , 2011. However, measurement of messenger RNA in urinary sediment is not always possible for routine examination because of RNA instability (Szeto et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A whole‐stream, early morning, urine sample at the time of renal biopsy was collected for the gene expression study . Briefly, the urine samples were centrifuged at 1650 g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been reported that quantification of messenger RNA expression of certain target genes in urinary sediment by reverse transcription became possible, and real‐time quantitative polymerase chain reaction (RT‐qPCR) may be a valuable noninvasive method for studying kidney diseases . We previously examined mRNA expression of transcriptional factors for the differentiation of helper T lymphocytes toward Th1, T‐bet and Th2, GATA‐3 in urinary sediment of children with IgAN and purpura nephritis (PN), and found that newly diagnosed cases showed a higher expression of T‐bet in urinary sediment compared to controls, and that this higher expression was associated with positive staining of T‐bet protein in renal biopsied tissue .…”
mentioning
confidence: 99%
See 1 more Smart Citation